MODEL ANALYSIS OF PURCHASE DECISION - Sembiring, Malikuddin (Dinasti Publisher, 2020)
Low light brick purchasing decisions constructs and real estate companies in Jakarta Provincial allegedly caused by product, distribution, promotion and customer value are still low. The purpose of this research is to Determine and analyze the effect of product, distribution, and promotion of partial or jointly to customer value. To Determine and analyze the effect of product, distribution, promotion and customer value partially or jointly to the purchasing decision. The population in this research amounted to 964 project managers of 241 construction and real estate companies in Jakarta. The method used in this research method was a descriptive survey and explanatory survey with a sample size of 295 respondents, and the data to the analysis methods used are SEM (Structural Equation Modeling) with 8.70 lisrel use application. Based on the results of the research, the following research findings product Obtained a positive and significant effect on customer value. Distribution of significant effect on customer value. Promotion significant effect on customer value. Product, distribution, and promotion together significant effect on customer value is equal to 47% while the remaining 53% is influenced by other factors. Partially promotion of the most dominant effect on customer value. The product does not affect the purchase decision. Distribution of positive and significant effect on purchasing decisions. Promotion of a positive and significant impact on purchasing decisions. Customer value of positive and significant effect on purchasing decisions. Product, distribution, promotion and customer value together positive and significant effect on purchasing decisions is equal to 81% while the remaining 19% are influenced by other factors. Partially customers value the most dominant influence on purchase decisions.